Equine placentitis is associated with a downregulation in myometrial progestin signaling†. Issue 1 (10th April 2019) - El-Sheikh Ali, Hossam; Legacki, Erin L; Loux, Shavahn C; Esteller-Vico, Alejandro; Dini, Pouya; Scoggin, Kirsten E; Conley, Alan J; Stanley, Scott D; Ball, Barry A
Abstract: The current study aimed to elucidate the mechanisms underlying myometrial activation during equine placentitis related to progestogens and the progesterone receptor signaling pathways. Placentitis was induced via intracervical inoculation with Streptococcus equi ssp zooepidemicus in mares at approximately 290 days of gestation (placentitis group; n = 6) with uninoculated gestationally matched mares as controls (n = 4). Mares in the placentitis and control groups were euthanized, and myometrial samples were collected from two regions: region 1—parallel to active placentitis lesion with placental separation in placentitis group (P1) or caudal pole of the placenta in control group (C1); and region 2—parallel to apparently normal placenta without separation in placentitis group (P2) or uterine body in control group (C2). In the current study, SRD5A1 and AKR1C23, which encode for the key P4 metabolizing enzymes, were downregulated in P1 in comparison to C1, C2, and P2, and this was associated with a decline ( P  < 0.05) in 5αDHP, allopregnanolone (3αDHP), and 20αDHP in P1 in comparison to C1. Further, myometrial expression of PR was downregulated ( P  < 0.05) in P1 in comparison to C1 and P2, and this was associated with activation of the inflammatory cascade as reflected by significant upregulation of IL-1β and IL-8 in P1 in comparison to C1, C2, and P2, and supported by increased tissue leukocytes in P1 in comparison to C1. In conclusion, equine placentitis is associated with a localized withdrawal of progestins and a downregulation of the PR in the myometrium concomitant with upregulation of inflammatory cytokines and subsequent myometrial activation. Abstract : This is the first report elucidating that equine placentitis is associated with a localized myometrial progestin withdrawal, as well as a functional withdrawal of progestins concurrent with a localized inflammatory response.